Leukocytic endogenous mediator in Crohn's disease. - Solomons, N W (1978)
Reduced concentrations of plasma zinc associated with elevated levels of serum leukocytic endogenous mediator activity were found in 17 patients hospitalized with acute exacerbation of Crohn's disease. Neither the decrease in plasma zinc nor the increase in leukocytic endogenous activator activity in nine outpatients with quiescent disease was significant. Leukocytic endogenous mediator activity may be increased in inflammatory conditions as well as in microbial infections. Although zinc deficiency may be common in patients with Crohn's disease, exclusive reliance on circulating zinc levels to assess zinc nutriture in active Crohn's disease may be misleading.